ADOLESCENT REPRODUCTIVE HEALTH IN MAJOR ETHNIC GROUPS IN EASTERN SIBERIA LIVING IN COUNTRYSIDE - A. V. Labygina; E. Yu. Zagarskikh; L. V. Suturina; N. A. Kurashova (Acta Biomedica Scientifica)
The paper presents the results of the cross-sectional epidemiological study of 96 teenagers of 14-17 years old of Mongoloid and Caucasoid populations living in countryside (village Bayanday, Irkutsk region). 3 ethnic groups were divided: 62 Mongoloid (Buryats, 65.3 %), 17 children of mixed marriages (metises; 17.9 %), 17 Caucasians (Russian, 16.8 %), including 47 boys(49.5 %, with an average age of 14,82 ± 0,79 years) and 49 girls (50.5 %, mean age 15,33 ± 0,15 years). The incidence of endocrine diseases, special ethnic characteristics of the endocrine and reproductive abnormalities and of certain hormones concentrations in Russian, mongrels and Buryat adolescents were established. Study of health major ethnic groups in Eastern Siberia, living in the countryside, set a higher frequency of reproductive abnormalities (with 43.7 % of girls and 31 % of boys). The high frequency of diseases of the endocrine system in Buryats and metises (50 % 52 %) compared to the Russian teens (12 %), basically hypothalamic syndrome of puberty and obesity. In 11-25 % of adolescents of studied ethnic and gender groups thyroid hyperplasia were established. However the median of FT4 and TSH were within the reference range, and the median of TSH was significantly higher in Russian teenagers both gender groups in comparison with the Mеtis and the Buryats. We have identified ethnic differences in the structure of the reproductive disease in boys: puberty delay and obesity, hyperprolactinaemia and testosterone decline, diagnosed more frequently in Mongoloids. Installed hormonal differences between groups of girls of the main ethnic groups suggest a role for testosterone in the reproductive disorders in Caucasians, prolactin the Mongoloid, which without appropriate correction can lead to infertility in reproductive age. The role of the environment on the development of hormonal disorders and the formation of the reproductive abnormalities in Caucasians, as identified by the hormonal changes teens Angarsk is 7-10 times higher than those found in adolescents Caucasian population living in countryside, which requires further study.